2021
DOI: 10.1021/acsami.0c21128
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature As-Grown Crystalline β-Ga2O3 Films via Plasma-Enhanced Atomic Layer Deposition

Abstract: We report on the low-temperature growth of crystalline Ga2O3 films on Si, sapphire, and glass substrates using plasma-enhanced atomic layer deposition (PEALD) featuring a hollow-cathode plasma source. Films were deposited by using triethylgallium (TEG) and Ar/O2 plasma as metal precursor and oxygen co-reactant, respectively. Growth experiments have been performed within 150–240 °C substrate temperature and 30–300 W radio-frequency (rf) plasma power ranges. Additionally, each unit AB-type ALD cycle was followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 67 publications
3
33
0
Order By: Relevance
“…Therefore, the GaN phase can be excluded and only the formation of α and γ-Ga The crystalline quality of the obtained Ga 2 O 3 nanomembranes is comparable to that inherent to ultrathin layers of Ga 2 O 3 obtained by using ALD techniques with subsequent annealing. A recent study reported on ICPE-ALD synthesis of 2D layers of β-Ga 2 O 3 on Si, sapphire, and glass [45]. The authors demonstrated evolution of XRD patterns from an amorphous layer to a fairly-crystallized one after ex situ treatment at 800 • C. Applying various growth and crystallization methods, it remains difficult to combine large-area uniformity and high crystal quality of β-Ga 2 O 3 structures.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the GaN phase can be excluded and only the formation of α and γ-Ga The crystalline quality of the obtained Ga 2 O 3 nanomembranes is comparable to that inherent to ultrathin layers of Ga 2 O 3 obtained by using ALD techniques with subsequent annealing. A recent study reported on ICPE-ALD synthesis of 2D layers of β-Ga 2 O 3 on Si, sapphire, and glass [45]. The authors demonstrated evolution of XRD patterns from an amorphous layer to a fairly-crystallized one after ex situ treatment at 800 • C. Applying various growth and crystallization methods, it remains difficult to combine large-area uniformity and high crystal quality of β-Ga 2 O 3 structures.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the temperature during growth depends mainly on the gallium precursor chosen [ 79 , 80 ]. Besides the conventional ALD, the plasma-enhanced atomic layer deposition (PEALD) further permits a lower deposition temperature and better Ga 2 O 3 film properties with very smooth surface roughness (<1 nm) [ 81 , 82 , 83 ].…”
Section: Gallium Oxide (Ga 2 O 3 )mentioning
confidence: 99%
“…[28] SiO 2 (PE-ALD) [7,24,25] β-Ga 2 O 3 (PE-ALD) [38] Silicon nitride (PE-ALD) [22,23,27,31,37,40] Plasma treatment (PE-ALD) [26] Electron treatment (CVD based) [36,39] GaN (CVD based) [42,44,45,55] InN (CVD based) [41][42][43]45,47,48,53,57,58] InGaN (CVD based) [49,51,54,56] InN nanopillars (CVD based) [46,50,52,55] The oxygen contamination overview provided in this introduction is followed by an experimental examination of some effects related to the surface modification of cathode materials by the generated plasma. In particular, we examine changes that have been observed for aluminum and stainless-steel cathodes.…”
Section: Materials (And Process) Referencementioning
confidence: 99%